A capoeira e os mestres - Paiva, Ilnete Porpino de (2007)
The Capoeira considered as a manifestation of the Popular Culture - inheritance of African peoples - is a cultural and social practice present in Brazil since the colonial time. This study is dedicated to the Capoeira and its masters. We work the Capoeira as a social field through the theoretical perspective of the Sociology of Pierre Bourdieu. We try to apprehend the social construction of the master, the legitimacy of his knowledge, the disputes and the representations that they ve elaborated over the space which was redefined for material and symbolic changes that occurred with the Capoeira through the last decades. The operating notions of social field, habitus, capital and tradition had been pertinent to think the power games , the social relations and the symbolic plots in the Field of Capoeira. From the methodological standpoint, although the interviews with the masters and the direct observation have had a special place in the research, other strategies had been used: researches in newspapers, thematic magazines and periodic, musical compositions and academic works. The performance of the masters in the process of reinvention of traditions has redefined their social place in relation to the previous generations. These are perceived as social actors responsible for the maintenance, dynamicity, affirmation, spreading and expansion of the capoeirístic practice